Alternatones A and B, two polyketides possessing novel skeletons from entophyte Alternaria alternate L-10. Issue 4 (3rd April 2022) - Zhang, Xuan; Liu, Xian-Xian; Xing, Yin-Nan; Zhang, Mei; Zhao, Yang; Wei, Yuan-Yuan; Zhang, Bo; Jiao, Rui-Hua
Abstract: On our ongoing searching for bioactive natural products derived from entophytes, two polyketides possessing novel skeletons, alternatones A–B (1 –2 ), were identified from the culture of Alternaria alternate L-10. Their structures were established by a combination of spectroscopic and single-crystal X-ray diffraction with Cu K a radiation. Alternatone A (1 ) exhibited cytotoxic activity against human hepatoma carcinoma HepG-2 cell line. The putative biosynthetic pathways for compounds 1 –2 were also proposed. Graphical abstract: UF0001